Judicial Considerations in Granting and Rejecting Child Madiyah Support Claims from a Progressive Legal Theory Perspective (A Normative Juridical Study of Decision No. 1172/Pdt.G/2018/PA.Smd. and Decision No. 41/Pdt.G/2014/PA Tkl.) - Reza, M Fahmi; Zahara, Fatimah; Khalid, Khalid (Journal of Law, Politic and Humanities, 2024)
This study titled "Judges' Considerations in Granting and Rejecting Child M??iyah Support Claims from a Progressive Legal Theory Perspective" focuses on analyzing judicial considerations in two Religious Court decisions, specifically Decision Number 1172/Pdt.G/2018/PA.Smd. and Decision Number 41/Pdt.G/2014/PA.Tkl. The research aims to identify how progressive legal theory influences judicial decisions regarding child m??iyah support and its implications for justice for neglected children. The study employs a normative juridical method with case study and comparative approaches, offering a deep exploration of the judicial reasoning that shapes outcomes in sensitive family law cases. The findings reveal that applying progressive legal theory can result in fairer and more responsive decisions to children's needs, highlighting the critical role of judicial discretion in interpreting the law beyond its literal text. In Decision Number 1172/Pdt.G/2018/PA.Smd., the claim was rejected on formalistic grounds, reflecting a rigid adherence to precedent, whereas in Decision Number 41/Pdt.G/2014/PA.Tkl., the claim was granted based on substantive justice considerations, prioritizing the child’s welfare. The study concludes by emphasizing the importance of applying progressive legal theory to ensure the protection of children's rights and achieve social justice within the context of Islamic and positive law in Indonesia. Furthermore, it suggests that a more dynamic and empathetic approach in judicial decision-making can significantly impact the realization of equitable outcomes in family law.